The Effect of Dhikr and Prayer on Anxiety in Preoperative Appendicitis Patients at Mokopido Tolitoli Hospital: Pengaruh Dzikir dan Doa Terhadap Kecemasan pada Pasien Pre Operasi Apendisitis Di RSUD Mokopido Tolitoli - Niswa Salamung; Iyan Iyan; Dg. Mangemba (Salando Health Journal, 2024)
Preoperative anxiety is a common psychological problem experienced by patients and can affect the surgical process and postoperative recovery. This study aims to measure the effect of dhikr and prayer on anxiety levels in preoperative appendicitis patients at Mokopido Tolitoli Hospital. The study used a quasi-experimental design with pre-test and post-test methods involving 60 patients, which were divided into two groups: the intervention group (30 patients) who received dhikr and prayer, and the control group (30 patients) who did not receive the intervention. The results showed that before the intervention, moderate anxiety levels dominated in the intervention group (50%) and control (54%), followed by severe anxiety of 40% and 36%, respectively. After dhikr and prayer, there was a significant decrease in the level of severe anxiety in the intervention group (40% to 10%) and an increase in the level of mild anxiety (10% to 60%). In contrast, the control group experienced only minor changes, with severe anxiety slightly decreasing from 36% to 30%. The data was analyzed with Chi Square. The results showed that there was a significant difference between the intervention group and the control group after the intervention (p < 0.05).  The results of this study indicate that dhikr and prayer are effective non-pharmacological interventions to reduce anxiety levels in preoperative patients with appendicitis. Therefore, dhikr and prayer can be applied as one of the psychological approaches in preoperative anxiety management.